Kinerja Bus Trans Padang Koridor IV dan Karateristik Penumpangnya - Salma Wahid Zaidir; Purnawan Purnawan (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2021)
In order to counterbalance movement of the city is by building mass transportation. However, the number of users who interested in using Trans Padang Corridor IV is relatively low. Analysis of the performance and passengers characteristics of the Trans Padang Corridor IV Bus is useful for improving performance based on the characteristics of the passengers. This study used a quantitative method in the form of observations, interviews, and also questionnaires which were described descriptively. Performance analysis was based on the decision of the Director General of Land Transportation No.SK.687/AJ.206/DRJD/2002. Based on the performance analysis (load factor, headway, waiting time, amount of buses, travel time, speed, capacity and cycle time) only waiting time was in accordance with the reference. For the passengers characteristics dominated by women, age range 36-45 years old, live in Lubuk Buaya urban village, private employee occupation, salary range <Rp. 500,000, do not have personal vehicle, the distance from the house to the bus stop is about 500m-1 km, work trip destination, reach the departure bus stop and final destination on foot, the time took from the departure to the destination is <5 minutes, the location of the departure stop is at the Lubuk Buaya bus stop, the destination area is Lubuk Buaya urban village, and the reasons for choosing the bus are because of the safety and the convenience of the bus.